Formulation of edible bird's nest (Aerodramus fuciphagus) from Central Kalimantan as skin whitening and moisturizing cream - Dita Ayulia Dwi Sandi; Eka Fitri Susiani (Wolters Kluwer Medknow Publications, 2021)
Context: Indonesia is the largest producer of edible bird's nest (EBN) in the world. Previous research proved that epidermal growth factor (EGF) was detected from edible bird's nest extract. EGF will increase the metabolism of skin cells and can lighten the skin EGF will increase the metabolism of skin cells and can lighten the skin. Aims: This research aimed to formulate and prove the lightening and the moisturizing effect of EBN cream on white mice. Materials and Methods: The 28 mice were divided into four group treatment. EBN 40% were formulated into cream with two formula types: water in oil (W/O) and oil in water (O/W). Before the treatment, white mice were exposed to UVA radiation until skin color level was 4. For 14 days, white mice were treated and observed skin color level and moisture content by skin analyzer. Results: The skin color level was 1 on day 8 (O/W), on day 9 (W/O), on day 8 (positive control), and showed skin color level was 4 on day 14 (negative control). The average water content on day 14 was 53.70 ± 1.21 (O/W), 50.13 ± 1.39 (W/O), 53.88 ± 0.88 (positive control), and 21.48 ± 2.90 (negative control). Conclusion: No significant difference was observed in lightening effect (Sig. 0.495) and moisturizing effect (Sig. 0.564) between O/W cream and W/O creams. W/O cream has good adhesion and O/W cream has good dispersion.